On the large-Q2 behavior of the pion transition form factor - Gernot Eichmann; Christian S. Fischer; Esther Weil; Richard Williams (Physics Letters B, 2017)
We study the transition of non-perturbative to perturbative QCD in situations with possible violations of scaling limits. To this end we consider the singly- and doubly-virtual pion transition form factor π0→γγ at all momentum scales of symmetric and asymmetric photon momenta within the Dyson–Schwinger/Bethe–Salpeter approach. For the doubly virtual form factor we find good agreement with perturbative asymptotic scaling laws. For the singly-virtual form factor our results agree with the Belle data. At very large off-shell photon momenta we identify a mechanism that introduces quantitative modifications to Efremov–Radyushkin–Brodsky–Lepage scaling.